Pengaruh Permainan Ular Tangga terhadap Pengetahuan dan Sikap dalam Menghadapi Menarche pada Siswi SDN Pringgowirawan 01 Sumberbaru Kabupaten Jember (The effect of snack and ladder game to the knowladge and attitude to confront menarche for the students of elementary school 01 Sumberbaru, Jember) - Dini Kurniawati; Devis Yulia Rohmana; Peni Perdani Juliningrum (UPT Percetakan dan Penerbitan Universitas Jember, 2017)
Menarche is the beginning of menstruation in young women and information about menarche is needed so that students can prepare themselves to confront menarche. The snake and ladder game is an educative game method that is appropriate for elementary school students. The purpose of this research was conducted to determine the effect of snake and ladder game on knowledge and attitude to confront menarche for elementary school students. This research is quasy experiment with two treatment group pretest-posttest design using 30 respondents with 15 respondents experimental group and 15 respondents comparing group (control). Data were analyzed by using Wilcoxon Signed Rank Test. The result showed that there was increasing knowledge of menarche by 40.1% from the treated group, and positive attitude confront of menarche increased by 46.6% after given intervention (p = 0.001/p <0.05), meaning that H1 was accepted, there are significant differences in knowledge and attitude between pre-test and post-test so the snake and ladder game affects the knowledge and attitude to confront menarche in the treated group. The snake and ladder game can improve knowledge and attitude to confront of menarche and learning method by using snack and ladder game can be one of the media to convey information to the elementary school students. Keywords : menarche, snack and ladder game